Tunnel fire testing and modeling : the Morgex North Tunnel experiment /: the Morgex North Tunnel experiment. ([2017]) - Borghetti, Fabio; Derudi, Marco; Gandini, Paolo; Frassoldati, Alessio; Tavelli, Silvia
No abstract available